The Influence of Ethics on Employee Achievement PT. Kalibaru Investama - Nasruji Nasruji; Frangky Yongky Turang; Betty Rahayu; Akhmad Nur Zaroni; Samuel PD Anantadjaya (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
This study was conducted at PT. Kalibaru Investama to determine how work ethics, experience, and culture affect employees' ability to do their jobs. The author wonders whether work culture, job experience, and work ethics all have simultaneous, significant effects on employee performance. The survey approach, along with a descriptive analytic methodology and verification, were used in this study. Obtaining data through distributing questionnaires to respondents. 41 PT. Berau Agrotech Cihaur personnel make up the study's sample. The method of non-probability sampling was used. Using the Windows version of SPSS 24, analysis with a traditional assumption test, multiple linear regression analysis, coefficient of determination, and hypothesis testing (partial and simultaneous tests).   The research's conclusions indicate that while job performance is exceptional, work ethics, experience, and culture are all positive. It suggests in part that job performance is positively and significantly influenced by work ethics, positively and significantly by work experiences, and positively and significantly influenced by work cultures. Showing how work culture, experience, and ethics have a positive and significant impact on work performance at the same time.